A case of severe complicated course of Taenia saginata with atypical localization of the helminth - S. S. Kozlov; S. P. Kokoreva; V. A. Vecherkin; V. B. Kotlova; L. A. Agisheva; E. A. Sklyarova; T. A. Korpusova; A. A. Drijakova (Журнал инфектологии, 2018)
Documented case of the clinical observations of the complicatedcourse of beef tapeworm infection (Taenia saginata) have a child 17  years of age. Three years ago, the patient first noticed the active  isolation of the cuttings from the anus. Other clinical symptoms were absent and the disease was latent. At the end of may 2017,  symptoms of an acute abdomen developed and an appendectomy  was performed on 03.06.2017. Diagnosis after surgery: acute  gangrenous perforative appendicitis, periappendicular abscess,  diffuse purulent peritonitis. 07.06.2017 was a single vomiting. In the vomit seen the segments of the flat worm. 09.06.2017,  segments of worms found in the feces. They were identified as  arthropods of Taenia saginata. From 14.06.2017 the patient’s  condition worsened, the temperature increased, there were pains in  the left half of the chest. In the following days the condition remained grave. According to CT (from 19.06.2017) helminth was determined in the  lumen of the left lower salt bronchus. Bronchoscopy was performed  (21.06.2017), which reduced the presence of signs of inflammation  of the left lower salt bronchus. Worms are not detected. Sputum  sowing was performed, but sputum microscopy was not carried out.  Ultrasound (23.06.2017) showed the presence of fluid in the left  pleural cavity. Puncture was performed and 70 ml of serous fluid was obtained. In the future, double-prosodical puncture which was obtained 600 and 500 ml of a yellow viscous exudate. On  29.06.2017, teniid eggs were found in sputum. Praziquantelum is  prescribed 25 mg / kg once. On 04.07.2017, the fourth puncture of  the pleural cavity was performed, 200 ml of light yellow effusion was obtained. In the days following the symptoms of pleurisy had disappeared and 10.07.2018, came recovery. Lung damage, which  developed as a result of aspiration of the arthroplasty Taenia  saginata was accompanied by a  rare dry cough and moderate  severe intoxication syndrome. The severity of the patient’s condition  was determined by severe respiratory failure and pain. Auscultation  of the wheezing was not. Over the lesion was sharply pronounced  weakened breathing. In the peripheral blood was determined by high ESR, moderate leukocytosis and no eosinophilia.